Principles - Dalio, Ray (Simon & Schuster, 2017)
Principles begins with novel ideas, its core is a clear, straightforward approach to decision making-including Dalio's innovative process of "believably weighting"-that anyone can apply no matter what they're seeking to achieve. The book also provides a blue-print for creating "an idea meritocracy that strives for meaningful work and meaningful relationships through radical truth and radical transparency", which is the reason for Bridgewater's success.